The Constitutional Right to Private Property Reflected in the Current Romanian Civil Law - Neculai Lungeanu (Journal of Danubian Studies and Research, 2018)
Relating to the constitutional principles and values, ensuring individual's right to private property, as evidenced by the extensive deposition of article 44 of the Constitution, represents, according to the Romanian legislator, a duty of the State that must prevent and punish the unlawful interference and contrary to the public order and morality. This constitutional right is linked to broader stipulations of civil law, the theory and timeliness of the private property right being intrinsic to human nature. Due to specific conceptual system, the private property rights allow an interdisciplinary approach, something which we aim at in this study, having as a starting point the constitutional text. The article uses as a research method the analysis of these incident texts of the law, of the punctual interpretation of the constitutional content of this subjective right, but also the legal limits imposed in specific cases.